ANATOMI DAN KUALITAS SERAT KAYU UTAP-UTAP (Aromadendron elegans Bl.) DAN TUJUH JENIS KAYU KURANG DIKENAL LAINNYA - Y l Mandang; Sissi Artistien (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Gross and anatomical features of Aromadendron elegans and seven lesser known wood species were observed and described for identification purposes and for evaluation of their suitable uses. Fiber dimension were also measured to evaluate their possible uses for pulp and paper. Several important features for identification were detected: 1) oil cells and closely spaced parenchyma bands in Aromadendron elegans; 2) wood semi-ring porous in Melia dubia; 3) radial intercellular canal and septate fibers in Lannea coromandelica; 4) ray storied and druses crystals in Hibiscus tiliaceus; 5) ray very high and contain sheath cells in Baccaurea sp.; 6) ray homocellular uniseriate and included phloem in Dolichandrone spathacea ; 7) parenchyma aliform and confluent, prismatic crystals in chambered axial parenchyma of Acrocarpus fraxinifolius; 8) wood white, fibers with distinctly bordered pit, and prismatic crystals in chambered axial parenchyma of Flindersia australis. All wood species studied have density and considerable strength to be used for construction purposes. Aromadendron elegans, Melia dubia, and Flindersia australis have decorative appearance so they are suitable for furniture. Flindersia australis is white and has moderately fine texture so it could be usedfor